Carbon Isotopic and Lithologic Constraints on the Sources and Cycling of Inorganic Carbon in Four Large Rivers in China: Yangtze, Yellow, Pearl, and Heilongjiang - Shan, Sen; Luo, Chunle; Qi, Yuanzhi; Cai, Wei‐Jun; Sun, Shuwen; Fan, Di; Wang, Xuchen (Journal of Geophysical Research: Biogeosciences, 2021)
Transport of terrigenous carbon by rivers has been affected extensively by climate change and anthropogenic activities in China over the last few decades. Here, we present results on carbon isotopes (C-13, C-14) of dissolved and particulate inorganic carbon (DIC and PIC) and combined with major lithologic ions measured in the four largest rivers in China, namely, the Yangtze, Yellow, Pearl, and Heilongjiang rivers, to reveal the sources and transport of terrigenous inorganic carbon in the rivers. The DIC concentrations showed large variations in the four rivers and ranged from 253 to 3,122 mu M. The Yangtze, Yellow and Pearl rivers transported high DIC contents that had low Delta C-14 values of millennium-aged DIC and very old PIC; however, the Heilongjiang River presented a lower DIC concentration with much younger C-14 ages than the global average (1,100 mu M). The strong correlations between the DIC isotope values and major lithological ions (Ca2+ and Mg2+) suggest that chemical weathering played important but variable roles in controlling the production and fate of DIC in the rivers. Using dual isotopes and the MixSIAR model, we calculated that the chemical weathering of carbonate rocks contributed 95 +/- 5% of the riverine DIC to the headwater of the Yangtze River while silicate rock weathering and riverine organic matter respiration contributed 62 +/- 25% and 5 +/- 5% of the DIC in the middle and lower reaches of the river, respectively. In contrast, chemical weathering of silicate rocks contributed the dominant fraction of DIC in the Yellow (55 +/- 17%), Pearl (61 +/- 20%) and Heilongjiang (83 +/- 29%) rivers.
Keywords: Carbon cycle; Chemical weathering; inorganic carbon in large rivers; radiocarbon; stable carbon isotope

Sources and sink of black carbon in Arctic Ocean sediments - Ren, Peng; Liu, Yanguang; Shi, Xuefa; Sun, Shuwen; Fan, Di; Wang, Xuchen (SCIENCE OF THE TOTAL ENVIRONMENT, 2019)
The concentrations and carbon isotopic (C-13, C-14) compositions of total organic carbon (TOC) and black carbon (BC) were measured for four sediment cores collected from the shelf to slope in the Arctic Ocean. Contents of TOC and BC ranged from 0.46% to 1.94% and 0.04% to 0.13% by dry weight, and BC accounted for 3.5% to 15.2% of the TOC preserved in the shelf and slope sediments. Sediment of the Chukchi shelf contained relatively high BC contents compared with the sediments of the Arctic slope, suggesting strong influence from the river and terrestrial inputs to the shelf region. Radiocarbon measurements revealed that the ages of BC are in the range of 7330 to 29,700 years (before present) and they are 4093 to 7723 years older than the C-14 ages of TOC preserved in the same sediment depths. Based on an isotopic mass balance model, we calculated that fossil fuel combustion contributed 62-96%, and biomass burning contributed 4-38% of the BC pool in the sediments of the study area. This ``slow-cycling'' old BC is an important fraction of the inert organic carbon pool preserved in the sediments, and represents a significant sink of atmospheric CO2 and global carbon cycle. With the thawing permafrost caused by continuous global warming, the size of this BC pool mobilized and exported by rivers to the Arctic Ocean could increase in the future. (C) 2019 Elsevier B.V. All rights reserved.